Acute renal transplant rejection following nivolumab therapy for metastatic melanoma. Issue 2 (8th February 2021) - Tan, Brandon; Baxter, Mark; Casasola, Richard
Abstract : Cancers can develop the ability to evade immune recognition and destruction. Immune checkpoint inhibitors (ICIs) are drugs targeting these immune evasion mechanisms. ICIs have significantly improved outcomes in several cancers including metastatic melanoma. However, data on toxicities associated with allograft transplant recipients receiving ICI is limited. We describe a case of a 71-year-old woman who was diagnosed with metastatic melanoma 13 years after renal transplantation. She was commenced on the ICI nivolumab. She developed acute renal transplant rejection 15 days after administration of the first dose. She continues on haemodialysis but has demonstrated complete oncological response. This case demonstrates the risk of acute renal transplant rejection versus improved oncological outcomes. Patients and clinicians must consider this balance when initiating ICI therapy in allograft transplant recipients. Patients should be fully consented of the potential consequences of acute renal transplant rejection including lifelong dialysis.